Community Perceptions of BPJS Employment Socialization Conducted by Student Community Service Program in Semurut Village, Berau Regency - Merlin (ECO-BUILD, 2026)
This study investigates community perceptions of BPJS Employment socialization conducted by community service students in Semurut Village, Berau Regency. Using a qualitative approach, data were collected through observations and in-depth interviews with 23 informants representing informal workers. The findings show that the community generally perceived the socialization positively due to the use of simple language, approachable communication, and the relevance of BPJS Employment to their daily work risks. However, participants noted challenges in understanding technical terms and expressed the need for repeated explanations and practical demonstrations. Factors influencing perceptions included limited prior knowledge, the communicative style of the facilitators, and the perceived usefulness of the program. Participants recommended follow-up sessions, printed materials, visual examples, and involvement of BPJS officers. These results align with previous studies highlighting the importance of contextualized, continuous, and trust-based communication in social protection outreach.